Effect of nutritional factors on growth and L-asparaginase production by three thermophilic coprophilous fungi - Ajmeera, Shanthi Priya; Rao, Vankudoth Koteswara; Sreelatha, B.; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (Current Research in Microbiology Biotechnology, 2015)
The present study aimed to investigate the effect of nutritional factors on L-asparaginase production by three thermophilic caprophilous fungi (Thielavia terrestris, Malbranchea cinnamomea and Scytalidium thermophilum) was assessed in YES medium by substituting starch and L-asparagine so as to supply equal amount of carbon and nitrogen sources respectively. D-glucose, starch, maltose and mannitol were best source for growth and L-asparaginase production by all three thermophilic caprophilous fungi under investigation. Similarly L-asparagine, L-arginine, L-tyrosine and L-histidine were good nitrogen sources for both growth and L-asparaginase production. Production of the variance of the data showed the significant difference (P<0.05) among the three thermophilic caprophilous fungi with regards to carbon and nitrogen source.